TINJAUAN KELENGKAPAN PENGISIAN BERKAS REKAM MEDIS RAWAT INAP DI RUMAH SAKIT ISLAM AR-RASYID PALEMBANG TRIWULAN I TAHUN 2023 - Fadhlika Qoyum, Nur Inda; Wirani, Yessy; Syahfitri, Bela (LPPM STIKes Mitra Adiguna, 2025)
Medical record is a file that containingnotes and documents regarding the patient's identity, examination, action treatment and other services that have been provided to the patient. The purpose of this study was to get an overview of the completeness of filling in inpatient medical record files at Islamic Ar-Rasyid Hospital. The research method used in this study is a descriptive method with a quantitative approach. The population in this study were medical record of inpatients at the Ar-Rasyid Islamic hospital with a sample of 95 medical record, sampling using random sampling. The results showed that the completeness of filling in medical record files which included filling in patient identification components, important notes, author authentication and good records were (74%) complete and (26%) incomplete. Factors affecting completeness, namely the absence of standard operating procedures and the absence of punishment for health workers who do not fill out a complete medical record.